2023
DOI: 10.1007/s13165-023-00442-5
|View full text |Cite
|
Sign up to set email alerts
|

Eco-packaging in organic foods: rational decisions or emotional influences?

Alessia Lombardi,
Giovanbattista Califano,
Francesco Caracciolo
et al.

Abstract: The introduction of biodegradable and compostable packaging has been a significant milestone in reducing conventional plastic use, particularly in sectors that prioritize sustainability like the organic food industry. This study explores the factors influencing the selection of such packaging, with a specific focus on the role of emotions in a representative sample of Italian consumers. Two models, the Theory of Planned Behavior (TPB) and the Rational-Emotional Model (REM), were evaluated and compared. The TPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Lastly, PBC can be defined as the extent to which an individual perceives having the abilities and/or control to perform the behavior and can predict it directly and indirectly (via intention). A large body of research has confirmed the high predictability of the TPB in various health domains [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, PBC can be defined as the extent to which an individual perceives having the abilities and/or control to perform the behavior and can predict it directly and indirectly (via intention). A large body of research has confirmed the high predictability of the TPB in various health domains [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%